006.2 High in vitro susceptibility to the novel spiropyrimidinetrione azd0914 among 873 contemporary clinical neisseria gonorrhoeae isolates in 21 european countries during 2012–2014. (13th September 2015) - Unemo, M; Ringlander, J; Wiggins, C; Fredlund, H; Jacobsson, S; Cole, M; Balla, Eszter; Barbara, Christopher; Borrego, Maria Jose; Brilene, Tatiana; Chisholm, Stephanie; Crucitti, Tania; et al.
Abstract : Introduction: Resistance in Neisseria gonorrhoeae has emerged to all antimicrobials available for treatment of gonorrhoea. The first gonococcal strains with high-level resistance to ceftriaxone, the last option for first-line empirical antimicrobial monotherapy, were recently described. Consequently, new treatment options are essential. In this study, the in vitro activity of the novel spiropyrimidinetrione AZD0914, a DNA topoisomerase II inhibitor, among contemporary consecutive clinical N. gonorrhoeae isolates obtained in 21 European countries was investigated and compared to the activities of antimicrobials currently or previously recommended for treatment. Methods: Consecutive clinical N. gonorrhoeae isolates (n = 873) cultured in 21 European countries during 2012–2014 were examined for their susceptibility to AZD0914. The MICs of AZD0914 were determined using agar dilution method. For comparison, the MICs of ceftriaxone, cefixime, azithromycin and ciprofloxacin were determined using Etest or agar dilution method. Results: For AZD0914, the MIC range, modal MIC, MIC50 and MIC90 was ≤0.002–0.25 mg/L, 0.125 mg/L, 0.064 mg/L and 0.125 mg/L, respectively. The MIC values were substantially lower than those of the fluoroquinolone ciprofloxacin and most other antimicrobials examined. No cross-resistance with any other examined antimicrobial was observed. Conclusion: The in vitro susceptibility to the novel spiropyrimidinetrione AZD0914 among 873 contemporary clinical isolates from 21 European countries was high and no cross-resistance to antimicrobials currently or previously used for gonorrhoea treatment was indicated. Additional studies investigating the in vitro and in vivo induction and mechanisms of AZD0914 resistance in gonococci, pharmacokinetics/pharmacodynamics in modelling/simulations and in humans, and performance in randomised controlled gonorrhoea treatment trials, are essential. Disclosure of interest statement: This work was funded by the Örebro County Council Research Committee and the Foundation for Medical Research at Örebro University Hospital, Sweden. We are grateful to Michael Huband and John Mueller, AstraZeneca for providing the AZD0914 compound and to ECDC, particularly Gianfranco Spiteri and Andrew Amato-Gauci, for funding and coordinating the European Gonococcal Antimicrobial Surveillance Programme (Euro-GASP).